2021
DOI: 10.1021/acsami.1c14118
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Microsphere-Loaded Non-mulberry Silk-Based 3D Bioprinted Vascularized Cardiac Patches with Oxygen-Releasing and Immunomodulatory Potential

Abstract: A hostile myocardial microenvironment post ischemic injury (myocardial infarction) plays a decisive role in determining the fate of tissue-engineered approaches. Therefore, engineering hybrid 3D printed platforms that can modulate the MI microenvironment for improving implant acceptance has surfaced as a critical requirement for reconstructing an infarcted heart. Here, we have employed a non-mulberry silk-based conductive bioink comprising carbon nanotubes (CNTs) to bioprint functional 3D vascularized anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 68 publications
(159 reference statements)
1
29
0
Order By: Relevance
“…Then, they also used microspheres loaded with IL-10, in order to immunomodulate the native MI environment with IL-10 delivery. They have concluded that IL-10 loaded microspheres increase oxygen availability and modulate the macrophages into anti-inflammatory M2 phenotype (131). It is a promising immunomodulatory study for the transplantation of biomaterial-based 3D construct into rat MI models for disease therapy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Then, they also used microspheres loaded with IL-10, in order to immunomodulate the native MI environment with IL-10 delivery. They have concluded that IL-10 loaded microspheres increase oxygen availability and modulate the macrophages into anti-inflammatory M2 phenotype (131). It is a promising immunomodulatory study for the transplantation of biomaterial-based 3D construct into rat MI models for disease therapy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Due to the potential, conductive materials have been used in smart biosensors, functional tissue engineering scaffolds, and implants. In extrusion-based bioprinting applications, conductive biomaterial inks can be formed by using different conductive materials including conductive polymers (e.g., polypyrrole [ 112 ] , polyaniline [ 142 ] , polythiophene [ 143 ] , and polyethylene dioxythiophene [ 144 ] ), conductive metal nanoparticles (e.g., gold [ 145 ] and silver [ 146 ] ), conductive carbon-based materials (e.g., carbon nanotube [ 147 ] and graphene [ 148 ] ), or ionic liquids [ 149 ] . Metal nanoparticles and carbon-based materials have long-term cytotoxicity, which can be a limitation for tissue engineering and regenerative medicine [ 112 ] .…”
Section: Classificationmentioning
confidence: 99%
“…Nowadays, nanomaterials combined with engineering 3D printing platforms to improve the acceptability of implants and reconstruct infarction hearts is a very promising research direction. Mehrotra et al used a conductive bioink containing carbon nanotubes (CNTs) to bioprint functional 3D vascularized anisotropic heart structures (Mehrotra et al, 2021). It was found that in addition to upregulating mature cardiac biomarkers, sarcomere formation, and beat rate, CNTs also promoted cardiomyocyte activity through immunofluorescence staining, polymerase chain reactionbased gene expression studies, and electrophysiological studies.…”
Section: Nanomaterials-mediated Cardiac Tissue Engineeringmentioning
confidence: 99%